Optimization of technological procedure for amygdalin isolation from plum seeds (Pruni domesticae semen) - Savic, Ivan M.; Nikolic, Vesna D.; Savic-Gajic, Ivana M.; Nikolic, Ljubisa B.; Ibric, Svetlana R.; Gajic, Dragoljub G. (Frontiers in Plant Science, 2015)
The process of amygdalin extraction from plum seeds was optimized using central composite design (CCD) and multilayer perceptron (MLP). The effect of time, ethanol concentration, solid-to-liquid ratio and temperature on the amygdalin content in the extracts was estimated using both mathematical models. The MLP 4-3-1 with exponential function in hidden layer and linear function in output layer was used for describing the extraction process. MLP model was more superior compared with CCD model due to better prediction ability. According to MLP model, the suggested optimal conditions are: time of 120 min, 100% (v/v) ethanol, solid-to liquid ratio of 1:25 (m/v) and temperature of 34.4 °C. The predicted value of amygdalin content in the dried extract (25.42 g per 100 g) at these conditions was experimentally confirmed (25.30 g per 100 g of dried extract). Amygdalin (>90%) was isolated from the complex extraction mixture and structurally characterized by FT-IR, UV and MS methods.